The Politics of the Second Vaccine: Debates Surrounding Ebola Vaccine Trials in Eastern Democratic Republic of the Congo - Myfanwy James; Joseph Grace Kasereka; Shelley Lees (Journal of Humanitarian Affairs, 2021)
Two experimental Ebola vaccines were deployed during the tenth Ebola epidemic (2018–20) in the Democratic Republic of the Congo (DRC). The first, the Ervebo vaccine manufactured by Merck, was used as part of a ring vaccination in the epicentre of the epidemic in North Kivu. In 2019, the prime- (Ad26.ZEBOV) and boost- (MVA-BN-Filo) vaccine manufactured by Johnson & Johnson (J&J) became the second vaccine against Ebola, deployed by the DRC-EB-001 vaccine trial in Goma, North Kivu. There was international debate as to the value and ethics of testing a second vaccine in an epidemic context. This article examines how this debate unfolded among actual and potential DRC-EB-001 trial participants in Goma. Drawing on ethnographic observation, interviews and focus groups, it explores how the trial was perceived and contested on the ground and situated in broader debates about the ethics of clinical trials, especially during the COVID-19 pandemic. We illustrate how debates around the ethics of clinical research are not simply centred on bioethical principles but are inseparable from local political dynamics and broader contests about governance, inequality and exclusion.